Kontribusi Kualitas Layanan Terhadap Kepuasan Pelanggan Pada Ghefa Therapy Center - Yusra Nginang; Asniwati Asniwati; Adrianah Adrianah; Rukmana Sari (Economics and Digital Business Review, 2024)
This research aims to determine the Contribution of Service Quality to Customer Satisfaction at Ghefa Therapy Center both partially and simultaneously. This study employs quantitative descriptive research. The population in this research is all customers of Ghefa Therapy Center, and the sample taken as respondents is 100 people, selected through random sampling. Data collection is conducted through observation techniques and structured questionnaires. The data analysis techniques used include descriptive analysis, validity test, reliability test, multiple linear regression analysis, correlation test, T-test, F-test, and classical assumption test. The research results indicate that simultaneously, the independent variables have a significant and positive effect with a contribution value of 31%, and the rest is influenced by other variables. Partially, all variables have a positive effect, with staff courtesy and information openness being the most significantly and positively influential.